A study of flow characteristics in a low-pressure ejector installation - Varsegova Evgenia; Osipova Lilia; Bugembe Daniel (E3S Web of Conferences, 2021)
Production processes sometimes are accompanied by the release of hazardous substances, the composition and volume of which is determined by the production technology. When designing ventilation systems for paint departments, special attention is paid to safety concerns, since all paint coatings are corrosive and flammable substances. Besides, solvent vapors are explosive. For local ventilation of painting chambers, it is rational to use safe exhaust systems with an ejector, which works sturdily, regardless of the release of flammable and explosive impurities. The ejector is simple in design and can operate in a wide range of changes in the parameters of the state of airflow. The model of the ejection unit is synthesized using the universal modeling package ChemCad, which contains a highly developed database of airflow parameters, which allows for solving various applied problems. Numerical modeling was carried out using the software package - FLUENT. In work, a calculation was carried out and a low-pressure ejector was designed for a typical painting booth. The calculation results are presented in the form of graphs and tables of pressures, velocities, flow rates in characteristic sections, pressure losses in the sections of the ejector installation.The ejection coefficient was also calculated.